Regional economics in Greece: A spatial analysis of business and population dynamics - Stella Manika; Evgenia Anastasiou (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: The economic crisis has led to a series of transformations of the economic and population base of the contemporary spatial units. The present study aims to highlight the indirect impact of the economic crisis on the operation and spatial footprint of the business network in a region with a slight decrease in its population dynamics in the decade 2001-2011. Design/methodology/approach: The methodological approach focuses (i) on the spatial and intertemporal observation of the change in the spatial footprint of the businesses and population of Greek Regional Units and (ii) in the identification of spatial clusters with similar behavior of business establishments or deletions (hot-cold spots). For the delineation of the profile of the spatial units, business demography indicators were created, while the analysis was based on spatial statistics methods and spatial autocorrelation indicators, such as the Global and local Moran's I. The panel data used for the present study relate to the establishment and deletions of businesses' during the period 2008-2018 as well as the population Censuses 2001-2011. Findings: It is evident that the crisis left its footprint in the Greek periphery. Examining the business network of two Greek Regional Units it is shown that during the crisis period a significant part of the businesses opened ceased in the early years after. Moreover, until 2016 there is a negative balance between business births and deaths. Especially Volos and Skiathos, despite that they presented an increase in their population, show higher intensity of businesses' deaths until 2014 than those of the establishments; after 2015 it is observed an inverse trend with positive establishments balance.The most important finding that confirms that space is not neutral is the autocorrelation in death rates in neighboring municipalities with simultaneous population decline. Research limitations/implications: The dependence of the external boundaries of a spatial entity on a neighboring one contributes to the possible effect on spatial patterns. In the present study, the spatial autocorrelation of the establishments and deletions of the businesses of Magnesia and the Sporades was examined, however, the influence of the adjacent area (the Regional Units of Larissa and Fthiotida) was not taken into account due to non-availability of the necessary data. Originality/value: The present study contributes to theory by highlighting the impact of the economic crisis in the footprint of a regions' business ecosystem. The added value lies in the connection and dependence of regional economies and populations with space. Future research could build on this study by examining business behavior in other spatial units. Furthermore, this study could be additionally used by policymakers to potentiate awareness of the local development, revitalization, and depopulation challenge.
Keywords: J1; R3; 330; Business Demography; Population; Regional Economics; Spatial Statistics; Global Moran's I; LISA; Greece